2002
DOI: 10.1034/j.1399-3054.2002.1140304.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex

Abstract: Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 36 publications
(68 reference statements)
5
66
0
1
Order By: Relevance
“…No clear inhibition of enzyme activities was detected during the drought period. Instead, remarkable between-tree variability was observed as reported in a previous study on mono-TPS activity in Q. ilex leaves (Fischbach et al, 2002). …”
Section: Seasonal Variation Of Monoterpene Synthase Activitiesmentioning
confidence: 76%
See 1 more Smart Citation
“…No clear inhibition of enzyme activities was detected during the drought period. Instead, remarkable between-tree variability was observed as reported in a previous study on mono-TPS activity in Q. ilex leaves (Fischbach et al, 2002). …”
Section: Seasonal Variation Of Monoterpene Synthase Activitiesmentioning
confidence: 76%
“…Correspondingly, Staudt et al (2003) found no increase of E S with increasing leaf age but rather a decrease or no change in E S of Q. ilex leaves. Similarly, Fischbach et al (2002) observed lower enzyme activities in 1-year-old than in current-year Q. ilex leaves. Another possibility is that caterpillar feeding in 2005 induced increased emissions in the non-attacked 1-year leaves.…”
Section: Discussionmentioning
confidence: 91%
“…A seasonal pattern of monoterpene emissions was also observed to depend diurnally and seasonally from light and temperature (Sabillon and Cremades, 2001) and phenology (Staudt et al, , 2000Ciccioli et al, 2003). This is attributed to slow development of the capacity to synthesize isoprenoid synthases, the enzymes catalyzing the formation of isoprene (Wiberley et al, 2005) or monoterpenes (Fischbach et al, 2002). Thus, a low emission of isoprene and monoterpenes may be expected early in the season.…”
Section: Isoprenoid Emissionmentioning
confidence: 99%
“…One is the respective routine of the MEGAN model Müller et al, 2008), which applies an empirical adjustment based on the past 10 days of light and temperature to calculate emissions, and the other is the SIM model that derives the seasonal course of the isoprenoid forming enzyme activity, which is closely related to potential emission, explicitly from the previous days climatic conditions (Lehning et al, 2001). Only the latter model reflects the finding that seasonal changes in enzyme activity result from physiological production and destruction processes (Lehning et al, 1999;Loreto et al, 2001;Fischbach et al, 2002;Mayrhofer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%